BIM data processing for project management - Lee, Wai Chi (Nanyang Technological University, 2022)
With the rapid development of the construction industry and computational technology, the digital delivery (IDD) in construction has been developed and started to be adopted by big players. However, for smaller players, such adoption is still far fetch due to lack of expertise in utilising the IDD tools. This project tried to look into one of the important IDD tool – 4D BIM, or project schedule management, to investigate the challenges from domain user perspectives and to see if there are critical bottle neck that needs to be tackled. In the process of building design, construction programme and operation, multiple software are needed, and it is difficult to share, exchange and store data between different software for multiple parties and multiple professions, resulting in a disconnection of data flow between different stages and project personnel. Such data exchange required both domain knowledges as well as software customisation capabilities. This leads to the 4D BIM is not widely used especially for small players that do not have much inhouse capabilities. Upon closer scrutiny, it is observed that key technical challenge in utilising 4D BIM is transferring critical data from 3D model components to planning application and linking these data with the timeline information. If this can be done, current 4D software can then be utilised to perform simulation as well as visualising the construction sequence. At the same time, since data are linked with timeline, cost data can also be added and 5D applications can be easily deployed. This study explores ways to make use of Application Programming Interface (API) and visual programming tools, to facilitate critical data transfer and linking process, albeit semi-automatically, so that 4D and 5D BIM can be utilised by domain users, without much programming knowledge requirements.